Cabo Verde : Technical Assistance Report-Monetary and Financial Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
At the request of the IMF's African Department (AFR) and the Bank of Cabo Verde (BCV), a monetary and financial statistics (MFS) remote technical assistance (TA) mission from the IMF's Statistics Department (STA) took place during January 18-29, 2021. The main objective of the mission was to assist the BCV in (i) reconciling the monetary accounts disseminated by the BCV with the monetary statistics submitted to STA for dissemination through International Financial Statistics and for internal use, in particular within AFR; (ii) improving the collection of data on sectoral distribution of credit by economic activity; and (iii) implementation of the IMF's 2016 Monetary and Financial Statistics Manual and Compilation Guide (MFSMCG).The work of the mission was facilitated by the excellent collaboration of the BCV's staff, in particular the Statistics and Economic Studies Department (DEE). The officials met during the mission are listed in Appendix I.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Cabo Verde